2002
DOI: 10.1107/s0907444902011642
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a complex of the potent and specific inhibitor BW284C51 withTorpedo californicaacetylcholinesterase

Abstract: The X-ray crystal structure of Torpedo californica acetylcholinesterase (TcAChE) complexed with BW284C51 {CO[ÐCH 2 CH 2 ÐpC 6 H 4 ÐN(CH 3 ) 2 (CH 2 ÐCH CH 2 )] 2 } is described and compared with the complexes of two other active-site gorge-spanning inhibitors, decamethonium and E2020. The inhibitor was soaked into TcAChE crystals in the trigonal space group P3 1 21, yielding a complex which diffracted to 2.85 A Ê resolution. The structure was re®ned to an R factor of 19.0% and an R free of 23.4%; the ®nal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
2
45
1
Order By: Relevance
“…However, BW284C51 did not exhibit inhibition difference between the purified AChEs from GH and WH populations. The current result is consistent with one previous report about Bactrocera dorsalis (Hsu et al, 2008), where one possible explanation was given for the fact that BW284C51 expressed weak effects on alteration of the interactions between the I214V and W121 sites of ace in B. dorsalis (Felder et al, 2002, Hsu et al, 2008. Though our results cannot give the comparisons of hydrolyzing ATChI and BTC, such good inhibitor specificities of the purified enzyme from the three populations also can indicate that the purified enzyme was a ''true'' AChE (Gao and Zhu, 2001;Ma et al, 2004).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…However, BW284C51 did not exhibit inhibition difference between the purified AChEs from GH and WH populations. The current result is consistent with one previous report about Bactrocera dorsalis (Hsu et al, 2008), where one possible explanation was given for the fact that BW284C51 expressed weak effects on alteration of the interactions between the I214V and W121 sites of ace in B. dorsalis (Felder et al, 2002, Hsu et al, 2008. Though our results cannot give the comparisons of hydrolyzing ATChI and BTC, such good inhibitor specificities of the purified enzyme from the three populations also can indicate that the purified enzyme was a ''true'' AChE (Gao and Zhu, 2001;Ma et al, 2004).…”
Section: Discussionsupporting
confidence: 95%
“…Based on k i values, results showed that purified AChE was highly sensitive to inhibition by eserine (a general inhibitor for both AChE and butyrylcholinesterase or BChE) and BW284C51 (a relatively specific inhibitor of AChE). Felder et al (2002) found that BW284C51 compound is considered to be a very specific inhibitor of Torpedo californica AChE by comparing the X-ray structure of a complex of the BW284C51 with TcAChE. However, BW284C51 did not exhibit inhibition difference between the purified AChEs from GH and WH populations.…”
Section: Discussionmentioning
confidence: 88%
“…5). These two compounds have the capacity to occupy both the active center gorge and the PAS, as shown for decamethonium or BW28C51 bound to crystalline TcAChE (34,41), although decidium may preferably occupy the PAS, as seen in the crystalline mAChE complex (19).…”
Section: Inhibition Kinetics and Binding Of Substrates And Reversiblementioning
confidence: 98%
“…Initial manual docking of an ACh molecule into the Torpedo californica (TcAChE) structure (4) was followed by structures of AChE complexes with competitive, reversible inhibitors (34 -38), covalent organophosphate or carbamate inhibitors (39), bifunctional inhibitors (20,32,34,40,41), PAS inhibitors (5,18,19), and the substrate analogue, trimethylammoniotrifluoroacetophenone (TMTFA) (42). The latter provides a close structural mimic of the substrateAChE tetrahedral transition state.…”
Section: Residue Trpmentioning
confidence: 99%
“…Finally, this predicted mode of Fab410 binding at the EeAChE PAS is also consistent with its competition with the large peptidic inhibitor Fas2 but absence of competition with the small organic inhibitors propidium, decamethonium, BW284C51, and the substrate acetylcholine when in excess (31). In fact, structural comparison of the crystalline Fab410-BfAChE and modeled Fab410-EeAChE complexes with crystalline mAChE or TcAChE complexes with acetylcholine (8,9) and propidium (18) and with the bifunctional ligands BW284C51 (63) and decamethonium (62) points to only one critical steric clash occurring between the propidium alkyl chain and Lys 57 in Fab410 CDR H2 (data not shown). This observation along with the greater improvement of propidium binding observed for the M70Y mutant of BfAChE compared with its K285D mutant (38) also largely supports our model of the Fab410-EeAChE complex.…”
Section: Evidence For Coexisting Open and Closed States Of A Back Doomentioning
confidence: 53%